Effect of photoinitiator on chain degradation of hyaluronic acid - Bo Min Hong; Su A Park; Won Ho Park (Biomaterials Research, 2019)
Abstract Objectives Photocrosslinking systems of polymers have been widely studied using UV or visible light irradiation. However, the photodegradation behavior derived from light irradiation was rarely reported, comparing with the photocrosslinking. In this study, the tyramine-modified hyaluronic acid (HA/Tyr) hydrogel was prepared using riboflavin (RF) as a photoinitiator, and the degradation behavior of HA by the reactive oxygen species (ROS) generated in photochemical process was investigated. Materials and methods The HA/Tyr conjugate was synthesized by EDC/NHS chemistry to introduce phenol group. Degree of substitution (DS, %) of phenol group to HA molecule was about 25%. The structural change of HA/Tyr was measured by proton nuclear magnetic resonance (1H-NMR) and attenuated total reflectance infrared spectroscopy (ATR-FTIR), and the rheological properties of photocrosslinked HA/Tyr hydrogel were investigated by rheometer. Results The HA/Tyr solution with 25% substitution formed a stable hydrogel via visible light irradiation in the presence of RF photoinitiator. Rheological data of HA/Tyr solution showed that the storage modulus (G’) was increased with increasing HA concentration. Additionally, it was found that RF initiated by visible light irradiation induced the degradation of HA molecular chain, and consequently reduced the viscosity of HA/Tyr solutions. Conclusion The results indicate that RF-based photoinitiator system caused the degradation of HA molecule by ROS generated in photochemical process as well as the crosslinking of HA/Tyr.